Foreign direct investment in Java Island, Indonesia - Ropinggi; Saud, Mohammad Basir; Melan, Mustakim (Klibel, 2012)
Globalization as well as an autonomy give the opportunities and challenges for every nation, region or area in the case of attracting foreign investor so that ready to inculcate its investment especially in Java Island, Indonesia.In fact, as we know that foreign direct investment (FDI) in every province in Indonesia are different in term of monetary.The main aim of this research is to identify the critical factors affecting the success of FDI inflow into Java Island and to determine whether locality is one of the main factors that affecting the success of FDI inflow into Java Island.This research used primary data and secondary data in getting the findings.The research reveals that productivity, state minimum wage, population, inflation, and incentive are among other factors identify in attracting inflow of FDI in Java Island.It is clearly stated that through F test, the critical factors affecting the success of FDI inflow into Java Island are population, state minimum wage, productivity, inflation, incentive, and location variables.Meanwhile from the t test, it shows that population, productivity and inflation play important roles in determining the inflow of FDI to Java Island. In addition, the location’s variable should be carefully considered among other things in order to facilitate foreign investors by improving or enhancing local resources or facilities, and having good network and infrastructure (logistics).